Antipsychotics, cognitive decline and death in Alzheimer's disease: the London and South‐East Region Alzheimer's Disease longitudinal study - Ames, D (BMJ Group, 2007)
The LASER‐AD study provides limited reassurance in relation to the occasional prescription of novel antipsychotics to elderly people with dementia